2011
DOI: 10.1055/s-0031-1297367
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Venous and Arterial Thrombosis: A Review of the Literature from a Causal Perspective

Abstract: Venous thrombosis and arterial thrombosis are traditionally regarded as two different diseases with respect to pathophysiology, epidemiology, and treatment strategies. Research findings of the past few years suggest that this categorical distinction may be too strict. However, whether the described relationship between venous and arterial thrombosis is real or a result of other factors such as confounding, chance, or bias is still unclear. In this review, we discuss the current literature while using causal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 58 publications
2
62
1
1
Order By: Relevance
“…Two recent large cohort studies found that cardiovascular risk factors obesity and smoking were also risk factors for VTE [15,16]. However, others suggested that this increased risk may be therapy related [17] or that a local inflammatory response, induced by VTE, may accelerate atherosclerosis [8]. In our study, patients without PE had somewhat higher amounts of CAC and TAC than did patients with PE (either unprovoked or all patients with PE).…”
Section: Resultsmentioning
confidence: 42%
“…Two recent large cohort studies found that cardiovascular risk factors obesity and smoking were also risk factors for VTE [15,16]. However, others suggested that this increased risk may be therapy related [17] or that a local inflammatory response, induced by VTE, may accelerate atherosclerosis [8]. In our study, patients without PE had somewhat higher amounts of CAC and TAC than did patients with PE (either unprovoked or all patients with PE).…”
Section: Resultsmentioning
confidence: 42%
“…4,5 Whether VT is causally associated with CVD is under debate. 6 Two prospective population-based cohort studies, the Atherosclerosis Risk in Communities and the Cardiovascular Health Study, 7,8 failed to confirm the association found earlier between atherosclerosis and VT. Furthermore, the increased risk of CVD after VT could be confounded by shared risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, an increased body mass index (BMI), smoking, chronic disease, malignancy, and (genetic) thrombophilia have all been found to increase the risk of both VT and CVD. 6,9,10 However, either because of a lack of information on classical cardiovascular risk factors (apart from age and sex) or because of a broad definition of CVD (eg, otherwise unexplained death, angina, transient ischemic attack, and angioplasty), no study has yet provided estimates of the risk of myocardial infarction and ischemic stroke after VT adjusted for shared risk factors. [3][4][5]11 In addition, other health determinants that may affect the risk of both VT and CVD, such as socioeconomic status, diet, and alcohol consumption, have not previously been taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Although venous and arterial thrombosishave traditionally been considered distinct pathophysiologic entities, the two disorders have many features in common, and there is evidence that persons with venous thrombosis may be at greater risk for arterial events 5 . On the other side, the association of peripheral venous disease with arterial endothelial dysfunction was recently found 6,7 .…”
Section: Introductionmentioning
confidence: 99%